2019
DOI: 10.1071/ah17042
|View full text |Cite
|
Sign up to set email alerts
|

Bridging existing governance gaps: five evidence-based actions that boards can take to pursue high quality care

Abstract: To explore the impact of the organisational quality systems on quality of care in Victorian health services. During 2015 a total of 55 focus groups were conducted with more than 350 managers, clinical staff and board members in eight Victorian health services to explore the effectiveness of health service quality systems. A review of the quality and safety goals and strategies outlined in the strategic and operating plans of the participating health services was also undertaken. This paper focuses on the data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 23 publications
1
10
0
Order By: Relevance
“…The IHI implementation scale was completed as a self-assessment and so may reflect internal views that "all is well". This was supported by previous findings that few of our study hospitals were aware of the gap between board and executive aspirations for high-quality care and the translation to point of care quality (Leggat and Balding, 2017a). The lack of association with the quality indicators and scales completed using objective information may suggest that these measures were not able to track subtle changes in organisational quality over the three-year period.…”
supporting
confidence: 86%
See 1 more Smart Citation
“…The IHI implementation scale was completed as a self-assessment and so may reflect internal views that "all is well". This was supported by previous findings that few of our study hospitals were aware of the gap between board and executive aspirations for high-quality care and the translation to point of care quality (Leggat and Balding, 2017a). The lack of association with the quality indicators and scales completed using objective information may suggest that these measures were not able to track subtle changes in organisational quality over the three-year period.…”
supporting
confidence: 86%
“…While there have been studies suggesting an association between board commitment to quality and organisational quality of care ( Jha and Epstein, 2010), a 2010 systematic review suggested that board monitoring of QI activities was related to QI in some studies, with impact on some QI indicators, but not others (Kaplan et al, 2010). Recent reviews around the world have questioned the effectiveness of board governance of quality (Francis, 2010;Garling, 2008;Mannion et al, 2016; Review of Hospital Safety and Quality Assurance in Victoria, 2016), leading to more information on exactly what governing bodies need to do to ensure high-quality care delivery ( Jones et al, 2017;Leggat and Balding, 2017a). Hospital governing boards are accountable for the overall quality and safety of care that is provided in their organisation (Auditor General Victoria, 2005;AICD, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In hierarchical health care organizations, the institution’s board of directors bears the ultimate responsibility for institutions’ functioning. In some jurisdictions, boards are not fully meeting their governance requirements for high-quality, safe-care delivery [ 23 ]. The data strongly support that physician engagement with their health care institution improves patient safety [ 24 ].…”
Section: Obstacles To Develop High-performance Teams Involving Physiciansmentioning
confidence: 99%
“…The board must act to ensure high-performance teams and ensure physician involvement. These actions focus on an organizational strategy for high-quality care, with the chief executive officer held accountable for evidence of successful implementation and monitored by the board [ 23 ].…”
Section: Obstacles To Develop High-performance Teams Involving Physiciansmentioning
confidence: 99%
“…In the hospital area, nursing has been facing challenges and demands that expose adaptation needs on the part of leaders and managers in the creation of different forms of management and in the search for work processes that promote a critical eye (1) . Such professionals are taking on executive positions that have become an essential part of organizations; and, after many advances, the perspective of patient care is strategically located at the executive level of the new structures (1) .…”
Section: Introductionmentioning
confidence: 99%